Influence of CYP2C19 genetic variants and smoking on dual antiplatelet efficacy in patients with coronary artery disease - Cheng, Yujing; Sun, Yan; Zhang, Dai; Ma, Xiaoteng; Liu, Chi; Hu, Chengping; Sun, Tienan; Zhao, Ziwei; Liu, Xiaoli; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2023)
Introduction: This study aimed to investigate the effects of smoking and CYP2C19 gene polymorphism on antiplatelet therapy to specify the most optimised and accurate antiplatelet therapy for different populations. Methods: This study included 6,353 patients with coronary artery disease (CAD). 2,256 (35.5%) were smokers and 4,097 (64.5%) were non-smokers. Patients carrying a CYP2C19*2 or *3 allele were considered loss-of-function (LOF) allele carriers. The medical history of patients who had undergone percutaneous coronary intervention (PCI) at Beijing Anzhen Hospital was recorded. The primary endpoint was major adverse cardiovascular or cerebrovascular events (MACCE) during the 6-month follow-up period. A cox regression model was used to assess the interactions between antiplatelet efficacy and CYP2C19 LOF allele carrier status, stratified by smoking status. Result: There were marginal significant associations between antiplatelet medication and CYP2C19 LOF allele carrier status for the MACCE recurrence risk (P = 0.065, respectively) among non-smokers. Compared to clopidogrel plus aspirin, ticagrelor plus aspirin reduced the MACCE recurrence risk in non-smokers (carrier: 6.0% vs. 2.0%, hazard ratio 0.298, 95% confidence interval 0.204–0.635, P <0.0001; non-carrier: 5.8% vs. 2.1%, hazard ratio 0.358, 95% confidence interval 0.189–0.678, P = 0.002), and not in smokers. Similar results were discovered regarding the recurrence rate for hospitalisation for ischemic cardiac events in non-smokers. No apparent difference was discovered in the bleeding events in either group. Conclusion: In patients with CAD after PCI, a marginally significant interaction between CYP2C19 LOF allele carrier status and antiplatelet effectiveness was observed in non-smokers. This interaction was not observed in smokers. In non-smokers, ticagrelor plus aspirin lowered the MACCE recurrence risk in CYP2C19 LOF allele carriers and non-carriers compared with clopidogrel plus aspirin alone. The efficacy of antiplatelet therapy varies between CYP2C19 LOF allele carrier status. However, caution should be used to interpret our results considering the many limitations of our investigation.